Entre tâche et activité : analyse des échanges langagiers d'élèves de cycle 3 lors de l'utilisation d'un outil de correction orthographique - Prisca Fenoglio; Catherine Brissaud (Nantes Université, 2020)
In the pedagogical scenario Twictée, created by teachers, primary and secondary school classes exchange short dictations (called « twictées ») and corrections of the dictations received (called « twoutils »). The latter are the heart and specificity of the scenario. Their intended goal is to help students normalize and automatize their orthographic knowledge through the explanation and categorization of the corrections in a set written format. This study enquires into this goal, through the analysis of verbal interactions of grade 4-6 students in five classes, during the process of making the « twoutils », with a particular attention to students with spelling difficulties. Results show that students' verbal interactions are, overall, repetitive rather than reflexive and identify variations among steps (ie. explanation vs categorisation of the correction of the spelling mistake), classes and levels of spelling performance. Based on these results, we discuss the learning processes fostered by the « twoutils » and make some proposals in order to improve their efficiency for all students.